Tegen de natuur? = Against Nature? - Wennerscheid, Sophie (CAHIER VOOR LITERATUURWETENSCHAP, 2019)
The ways in which sexuality is conceptualized, narrated, mythologized and practised vary greatly across historical periods and cultures. But however variously sexuality has been constructed over centuries, it has very often been regarded as something that quickly changes into something unnatural. It is the aim of this thematic issue to focus on those ambivalent moments of transformation and re-evaluation.